Swimming behavior of pseudomonas aeruginosa studied by holographic 3D tracking - Vater, Svenja Mareike; Weiße, Sebastian; Maleschlijski, Stojan; Lotz, Carmen; Koschitzki, Florian; Schwartz, Thomas; Obst, Ursula; Rosenhahn, Axel (PLOS ONE, 2014)
Holographic 3D tracking was applied to record and analyze the swimming behavior of Pseudomonas aeruginosa. The obtained trajectories allow to qualitatively and quantitatively analyze the free swimming behavior of the bacterium. This can be classified into five distinct swimming patterns. In addition to the previously reported smooth and oscillatory swimming motions, three additional patterns are distinguished. We show that Pseudomonas aeruginosa performs helical movements which were so far only described for larger microorganisms. Occurrence of the swimming patterns was determined and transitions between the patterns were analyzed.